Barriers against application of evidence-based medicine in general hospitals in Aseer Region, Kingdom of Saudi Arabia - Khalid S Al-Gelban; Yahia M Al-Khaldi; Abdullah M Al-Wadei; Ossama A Mostafa (Wolters Kluwer Medknow Publications, 2009)
Objective: To explore the attitudes of doctors in the general hospitals and their application of evidence-based medicine (EBM) and to identify the barriers that hinder its use. Subjects and Methods: This study included 346 doctors in the general hospitals of Aseer. A questionnaire was designed to assess their awareness as well as the barriers that hinder their practice of EBM. A visual analogue scale was used to assess their attitude. Results: The attitudes of doctors toward aspects of EBM were generally positive. However, their use of EBM sources and application were generally poor. The main reasons for retrieving evidence were to keep them up-to-date (72.8%) and to help make clinical decisions (70.2%). The least mentioned reason for evidence retrieval was research (41.9%). Review of textbooks was the main method of evidence retrieval (71.1%), while a database search was the method least used (22.8%). The main barriers to the practice of EBM practice were "lack of facilities" followed by "lack of time", while the barrier least mentioned was the "lack of interest". Conclusions: Although doctors have positive attitudes toward EBM, their knowledge and application of EBM need much improvement. The main barriers to their application of EBM are the lack of facilities and the lack of time. Recommendations: The necessary infrastructure for the application of EBM should be made available for all medical staff. There is a need for special courses and hands-on workshops in general hospitals to address the necessary knowledge and skills of EBM are essential.